PENGARUH LINGKUNGAN KERJA, BEBAN KERJA DAN KONFLIK KERJA TERHADAP STRES KERJA KARYAWAN PT. INTI MANUNGGAL SEJAHTERA ABADI - Thea Herawati Rahardjo; Choirun Nissa Nurdiyanti (Pasca Sarjana Universitas Satya Negara Indonesia, 2018)
To overcome the level of job stress employees need to consider several factors including work environment, workload and work conflict. This study aims to determine the effect of work environment, workload and work conflict simultaneously or partially to the employee work stress of PT. Inti Manunggal Sejahtera Abadi. The research sample are 44 production employees’. The multiple linear regression, t test and F test are used as the analysis techniques. The results showed that work environment, workload and work conflict simultaneously have a significant effect on employee’s job stress. While t test re sults indicate that workload and work conflict partially affect the employee's work stress, while the work environment has no effect.